The complexity of interpersonal physiology during rupture and repair episodes in the treatment of borderline personality disorder: a proof-of-concept multimethod single case study of verbal and non-verbal interactional dynamics - Høgenhaug, Stine S.; Steffensen, Sune V.; Orsucci, Franco; Zimatore, Giovanna; Schiepek, Guenter; Kongerslev, Mickey T.; Bateman, Anthony; Kjaersdam Telléus, Gry (Frontiers in Psychology, 2024)
The aim of this proof-of-concept multimethod exploratory single case study was to increase knowledge of the underlying mechanisms of alliance ruptures and repairs in Borderline Personality Disorder treatment across and within the psychotherapeutic treatment process. The multimethod included outcome assessment of patient self-reporting questionnaires (the Affect Integration Inventory, the Hopkins Symptom Checklist), observation-based ratings of sessions with the Rupture Resolution Rating System, quantitative analysis of heart rate variability using recurrence quantification analysis, and a qualitative multimodal interaction analysis of within-session dynamics.Results revealed how patterns of heart rate synchrony between patient and therapist reflected periodical patterns of emotional interaction corresponding to key therapeutic alliance processes throughout the treatment process. Particularly, heart rate synchronization and desynchronization corresponded with increasing rupture resolution ratings and positive outcome measures in the last part of the therapy process, indicating increased productivity and positive change. The qualitative microanalysis highlighted context sensitivity to alliance management within sessions. Physiological arousal was found to underlie important alliance processes, including emotion regulation, relatedness, security, empathic responding, sense-making, and validation in correspondence with different therapist verbal and non-verbal markers of emotional inference, formulations, nods, and initiated shared laughter, which among others identified as important means of action when addressing and negotiating ruptures.